Water-borne preservatives: CCA / Mohd Abdul Fatah Mustafa - Mustafa, Mohd Abdul Fatah (2005)
In this study, CCA as one of the popular preservative has been chosen. It has been used enormously throughout the world. It has been used since 19 century and commercially in wood industry through preservation process. It is an effective wood preservative. The effectiveness of CCA has been studied from many method and test. But it is not enough and practical. So many observation and analysis has been made through it experience of services. Also in my study the standard method that has been done is also available. So in this project it contains the accumulation of the important of CCA as wood preservatives.